Marker-assisted Backcrossing for Identification of Salt Tolerant Rice Lines - Moniruzzaman, M; Alam, MS; Rashid, JA; Begum, SN; Islam, MM (International Journal of Agricultural Research, Innovation and Technology, 2013)
SSR or microsatellite markers are proved to be ideal for making genetic maps, assisting selection and studying genetic diversity in germplasm. SSR markers are playing important role to identify gene for salt tolerance that can be helpful for plant breeders to develop new cultivars. The experiment was conducted during the period from July 2009 to November 2010 in the experimental field and Biotechnology Laboratory of Plant Breeding Division, Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh to identify salt tolerant rice line of BC1F1 progenies of Binadhan-5 x FL-478 using SSR markers. Salt tolerant genotype, FL-478 was crossed with high yielding variety, Binadhan-5. Randomly selected 40 BC1F1 progenies along with their two parents (Binadhan-5, FL-478 and F1) were genotyped with microsatellite or SSR markers for identification of salt tolerant rice lines. Parental polymorphism survey was assayed by 10 SSR markers and three polymorphic SSR markers viz., RM 336, RM 510, and RM 585 were selected to evaluate BC1F1 rice lines for salt tolerance. In respect of Primer RM 336, 11 lines were found as salt tolerant and 25 lines were heterozygous and 3 lines were susceptible. Primer RM 510 identified two tolerant, 14 heterozygous and 22 susceptible lines. And primer RM 585 identified 4 lines as tolerant and 35 lines as susceptible. Thus, these markers could be efficiently used in tagging salt tolerant genes, in marker-assisted selection and quantitative trait loci (QTL) mapping. The selected BC1F1 could be used for developing BC2F1 and BC2F2 and mapping genes for salinity tolerance. DOI: http://dx.doi.org/10.3329/ijarit.v2i2.14008 Int. J. Agril. Res. Innov. & Tech. 2 (2): 1-8, December, 2012